Directional spectral emissivity characterization and modeling of laser-patterned steel surfaces - Gabirondo-López Jon; González de Arrieta Iñigo; Soldera Marcos; Lasagni Andrés F.; Arredondo Iñigo; Igartua Josu M.; López Gabriel A. (EPJ Web of Conferences)
We present preliminary results on the fabrication of patterned surfaces by Direct Laser Interference Patterning and the characterization and theoretical interpretation of their infrared emissivities. The upgraded experimental method is capable of studying the full directional emission of samples under a controlled atmosphere at high temperatures. The effects of surface patterning can be quantitatively studied and modeled using a numerical method based on rigorous coupled-wave analysis (RCWA), a technique usually employed for periodic surfaces. The results show that laser interference patterning is capable of modifying the infrared emission of metallic materials, and that these changes can be accurately measured and numerically reproduced.